2022
DOI: 10.1177/03915603221107135
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative predictors for complications in patients with Xanthogranulomatous Pyelonephritis treated with nephrectomy

Abstract: Introduction: Xanthogranulomatous pyelonephritis is an inflammatory disease characterized by chronic obstruction and infection. This pathology is a life-threatening condition when surgical treatment is carried out. We decided to retrospectively evaluate whether there were perioperative factors that predict complications in patients who undergo nephrectomy. Methods: We reviewed all nephrectomies done in the period of 2013–2018, in a tertiary referral Hospital with the histopathological diagnosis of Xanthogranul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Montelongo-Rodríguez et al reported that anemia and the presence of renal abscess were associated with major complications. 14 Although anemia and renal abscess were present in our study population, we did not purposefully look for an association between these factors and the occurrence of major complications.…”
Section: Discussionmentioning
confidence: 95%
“…Montelongo-Rodríguez et al reported that anemia and the presence of renal abscess were associated with major complications. 14 Although anemia and renal abscess were present in our study population, we did not purposefully look for an association between these factors and the occurrence of major complications.…”
Section: Discussionmentioning
confidence: 95%